KESALAHAN EJAAN BAHASA INDONESIA DALAM DESKRIPSI KOLEKSI PADA MUSEUM DI BANTEN DAN IMPLEMENTASINYA SEBAGAI MODUL AJAR TINGKAT SMP - Lia Nadia; Ediwarman Ediwarman; M. Rinzat Iriyansah (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
The analysis of Indonesian spelling errors is part of the language error analysis unit, which refers to efforts to examine whether the use of Indonesian spelling is in accordance with linguistic rules. The findings of spelling errors in the descriptions of museum collections cannot be taken lightly, as museum collection descriptions serve as educational media for visitors. This study aims to serve as an educational and learning tool to raise awareness among language users to use Indonesian correctly in accordance with linguistic rules. The objectives of this study are to classify and describe the types and forms of Indonesian spelling errors found in the descriptions of museum collections in Banten; (2) to describe the factors that influence Indonesian spelling errors in the descriptions of museum collections in Banten; and (3) to explain the implementation of the analysis of Indonesian spelling errors found in the descriptions of museum collections in Banten in teaching modules for junior high school Indonesian language learning. The research method used was qualitative with a case study strategy. The research results found 390 spelling error data in 124 descriptions of collection objects in museums. The data included 209 data on letter usage errors, 53 word writing errors, 123 punctuation usage errors, and 8 writing errors in loanwords. There are four factors influencing spelling errors in museum collection descriptions: lack of attention to detail, lack of understanding of EYD V application, lack of mechanisms for monitoring and correcting writing, and lack of involvement from the Language Development and Promotion Agency. The findings and data sources from this research can be implemented as teaching materials in the ninth-grade Indonesian language curriculum, specifically in the descriptive text and writing elements modules. The analysis of spelling errors can certainly contribute positively to evaluation and learning for language users.